The Theatre of “Glass Puppetry” Enhanced With The Use of The Technology of Lighting - I Made Sidia (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2023)
The life of a Wayang Artist is an honorable role to have in the society of the Balinese people. Storytellers using the art of the wayang are highly respected, whose role in the community is to pass on the precious stories about the history, the culture and the spiritual heart of the Balinese people. The Wayang artist, known as the dalang goes on a life journey in sharing their philosophies through stories for the enrichment and soul of society. The process of internalization of the Puppet master from an early age through the world of wayang, forms a cognitive map of the creator who is immersed in the stories and characters of wayang art figures. The wayang artist continues to strive for innovation in form, exploring new techniques and exciting presentations, and with that in mind, the invention of the Glass Wayang enables the creator to explore the new technologies in developing a new way forward in the shadow puppet world. The process of creating Glass Puppets using the technology of lighting as a medium, opens one up to reflect on the mirroring of the self-image- to self-awareness and the inner workings our role in this human life Dramatic depictions of life processes are conveyed through the medium of glass puppets. Experiences and realities of life from the past until now. The search for identity is awakened. Wayang Kaca's work ranges from the making of various styles and forms of puppets supported by one hundred and six dancers accompanied by digital musical instruments (midi) and Bebonangan and Semarandhana gamelan. Digital musical instruments (midi) and gamelan are not only accompaniment but are an important part in providing a traditional and modern feel. The performance venue at Sanggar Paripurna Bona, Gianyar includes a side stage along with the traditional proscenium stage.  allowing for a full presentation for displaying this Glass Wayang work. The facilities the sanggar offers allow for all aspects of the creation process in developing, rehearsing, and presenting a final performance.